2017
DOI: 10.1007/s12550-017-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of fumonisins by endophytic strains of Tolypocladium cylindrosporum and its relation to fungal virus infection

Abstract: Fumonisins were first discovered in Fusarium verticillioides, a fungus associated to disease and asymptomatic infections in maize. Afterwards, other fungal taxa have been found to produce fumonisins. The entomopathogenic ascomycete Tolypocladium cylindrosporum has been isolated from soil and also as an endophyte from leaves of grasses. The objectives of this work were to determine the in vitro production of fumonisin B (FB) mycotoxins and the immunosuppressive compound cyclosporine A (CyA) in several strains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Tolypocladium cylindrosporum is a fumonisin-producing entomopathogenic fungus, which is also isolated as an endophyte from grasses. A survey of endophytic strains of this fungus showed a significant increase in fumonisin B 2 production in mycovirus-infected strains [ 60 ]. Similarly, Nerva et al [ 61 ] found that Aspergillus ochraceus virus (AoV), a partitivirus widespread in Aspergillus ochraceus , can cause an overproduction of the mycotoxin ochratoxin A (OTA).…”
Section: Introductionmentioning
confidence: 99%
“…Tolypocladium cylindrosporum is a fumonisin-producing entomopathogenic fungus, which is also isolated as an endophyte from grasses. A survey of endophytic strains of this fungus showed a significant increase in fumonisin B 2 production in mycovirus-infected strains [ 60 ]. Similarly, Nerva et al [ 61 ] found that Aspergillus ochraceus virus (AoV), a partitivirus widespread in Aspergillus ochraceus , can cause an overproduction of the mycotoxin ochratoxin A (OTA).…”
Section: Introductionmentioning
confidence: 99%
“…Mycoviruses have been found to affect fungal production of mycotoxins, with this effect notable at high temperatures. For example, mycovirus-infected grass fungus Tolypocladium cylindrosporum produced less fumonisin B (FB) than the virus-free strain [72], whereas mycovirus-infected Aspergillus clavatus isolates produced less patulin than control fungi [73]. Moreover, mycoviral infection in Fusarium graminearum has been associated with decreased deoxynivalenol production [74].…”
Section: Influence On Toxin Productionmentioning
confidence: 99%
“…; Zabalgogeazcoa et al . ). Whereas the larvicidal activity of T. cylindrosporum against species of genera such as Aedes , Culex , Culiseta and Ochlerotatus is well documented (Scholte et al .…”
Section: Introductionmentioning
confidence: 97%